Rationality of the Use of NSAIDS in Rheumatic Osteoarthritis Patients in Outpatient Singosari Health Center Pematangsiantar City - Wilson Samosir; Shofian Syarifuddin; Friska Simanihuruk; Evita Dora Br Sinukaban (PT Inovasi Pratama Internasional, 2022)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis Osteoarthritis (OA) is the most common form of arthritis found in the community, is chronic in nature, has a major impact on public health issues. a total of 213 arthritis patients, only 30 patients who met the inclusion criteria were due to incomplete medical record data or even loss of medical record data which caused the patient's medical record data to be incomplete. right indication, right drug, right dose, right route of administration, right patient) then the results of the analysis show that accuracy is 100% right, while for the right drug parameters it is still worth 53%. So it can be concluded that treatment for osteoarthritis patients when viewed from the right diagnosis, right indication, right dose, right patient, right drug, right method of administration at the Singosari Health Center cannot be fully rational.